The Diagnostic Yield of Open Lung Biopsy in relation to clinical and radiological features in Patients with Suspected Interstitial Lung Disease - Hussein, Saja A.; Sultan, Qasim M.; Nassr, Abdulrasool N.; Jameel, Basil F. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: The diagnosis of interstitial lung disease (ILD) is frequently delayed, because clinical clues are neglected and respiratory symptoms are ascribed to more common pulmonary diagnosis such as asthma and chronic obstructive pulmonary disease in the primary care setting.Objective: To evaluate the diagnostic yield of open lung biopsy in patients with suspected ILD in relation to clinical and radiological features.Patients and methods: Thirty-five patients were admitted with suspected interstitial lung disease (ILD), and scheduled for open lung biopsy (OLB) in Ghazi AL-Hariri hospital for surgical specialty, were included in this study. Data collected from the patient's files (who were subjected to open lung biopsies which had been histopathologically studied in the period from 1st of January 2013 to 31st of May 2015) and were studied retrospectively.Results: There were 11 (31.4%) males and 24( 68.6%) females, the mean age was 46±14 years , dyspnea was the common presenting symptoms in patients 24(68.6%) , dry cough was the presenting symptoms in10 (28.6%)patients , bilateral diffuse crepitations were heard in 20 (57.2%) patients, bilateral fine basal crepitation were heard in 11 (31.4%) , clubbing with bilateral fine basal crepitations heard in 4 (11.4%) ,chest-x- rays findings were: lower zone infiltration in 11 (31.4%), reticulonodular infiltration in 10 (28.6), nodular infiltration in8 (22.9%) and opacities in6 (17.1%). CT findings were: basal infiltration in11 (31.4%), reticulonodular infiltration in 10 (28.6%), nodular infiltration in 8 (22.9%) and ground glass appearance s in 6 (17.1%). Histopathological examination (obtained from Open lung biopsy) results were: had usual interstitial pneumonia (idiopathic pulmonary fibrosis) 21(60%), 7 (20%) metastasis, 5 (14.3%) pulmonary TB and 2(5.7%) broncho-alveolar cell carcinoma.Conclusion: Open lung biopsy can give a high diagnostic yield and confirm or alters the diagnosis in a significant number of patients with suspected interstitial lung diseases. The usual interstitial pneumonia pattern is the commonest histopathologic pattern seen in ILD patients. الخلفية: تشخيص أمراض الرئة الخلالي كثيرا ما يتأخر، لأنه يتم إهمال االاعراض السريرية والأعراض التنفسية, تعزى إلى تشخيص امراض  الرئة الأكثر شيوعاً مثل الربو ومرض انسداد الشعب الهوائية المزمن في إطار الرعاية الصحية الأولية.الهدف: تقييم العائد التشخيصي لخزعة الرئة المفتوحة في المرضى الذين يعانون من اشتباه في امراض الرئة الخلالي  بالسمات السريرية والإشعاعية.المواضيع والأساليب:  شملت الدراسة خمسة وثلاثون مريضا ممن لديهم  أمراض الرئة الخلالي المشتبه فيه، والمقررلهم خزعة الرئة المفتوحة (OLB) في مستشفى غازي الحريري للتخصصات الجراحية.تم جمع البيانات من ملفات المريض (الذي تعرض لفتح خزعات الرئة والتي درست الفحص النسيجي له للفترة من الأول كانون الثاني/يناير 2013 إلى 31 مايو عام 2015)، وقد تم  دراستهم  باثر رجعي .النتائج: اظهرت النتائج الذكور 11 (31.4%) والإناث 24(68.6%) ، كان متوسط العمرلهم 46±14 سنة، ضيق التنفس كان اكثر الأعراض الشائعة في 24 مريض  (68.6%) ، والسعال الجاف عند 10مرضى (28.6%) ، سماع قرقعة منتشرة  في كلا الرئتين  في20 مريض  (57.2%) ، سماع قرقعة  القاعدية في  كلا الرئتين في 11  مريض(31.4%)، تضخم اظافر اليد مع قرقعة قاعدية سمعت في 4 مرضى (11.4%)   ، وكانت نتائج أشعة الصدر ترشح في الجزء الاسفل للرئة عند  11مريض (31.4%)، ترشح شبكي- عقدي في  مرضى10 (28.6)، ترشح عقدي في 8 مرضى (22.9%) ونسبة تظليل في 6 مرضى (17.1%).  وكانت نتائج الأشعة المقطعية: ترشح القاعدية في11 مريض (31.4%)، ترشح شبكي عقدي في 10مرضى (28.6%)، ترشح عقدي في 8 مرضى (22.9%) ومظهر  زجاج الأرض s في 6مرضى (17.1%). وكانت نتائج الدراسة النسيجية التي تم الحصول عليها من خزعة الرئة المفتوحة: كان 21 (60%) الالتهاب الرئوي الخلالي المعتادة (تليف رئوي مجهول السبب)، 7مرضى ورم خبيث ثانوي (20%)، السل الرئوي5 (14.3%)وورم  الخلية السنخية القصيبية 2(5.7%).الاستنتاج: خزعة الرئة المفتوحة يمكن أن تعطي نتيجة تشخيصيةعالية ,حيث تؤكد أو تغير التشخيص في عدد كبير من المرضى الذين يعانون من أمراض الرئة الخلالي المشتبه فيهم. النمط المعتاد من الالتهاب الرئوي الخلالي هو نمط الأنسجة الأكثر شيوعاً ينظر في مرضى أمراض الرئة الخلالي.